Long-Term Multimodal Loading of Fiber-Based Magnetic Scaffolds for Hyperthermia Applications - Schneider, Karl; Slabu, Ioana (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
We designed and tested an experimental setup intended for medical device quality assurance, capable of multimodal loading of fiber-based magnetic scaffolds. These magnetic scaffolds are promising for hyperthermia treatment of hollow organ cancers. To approximate the physiological conditions during magnetic hyperthermia treatment, a multimodal load consisting of a thermal load, a hydrodynamic load, and a mechanical load was considered. The effect of the multimodal load on polypropylene fibers with embedded magnetic nanoparticles was analyzed to assess changes in the mechanical properties of the fibers. We demonstrate that the nanomodified PP fibers relax according to the Poynting-Thomson model.